INVESTIGATING PROFESSIONAL ROLE IDENTITIES OF EFL PRE-SERVICE TEACHER THROUGH PHOTOVOICE BASED SELF REFLECTION IN TEACHING PRACTICUM - Devi Novitasari; Abd Rahman (STKIP PGRI Jombang, 2020)
Much research has confirmed the important role of reflection to promote pre-service teachers’ professional role identity in their teaching practices. A myriad of reflection tools has been used to promote teachers’ professional identity including journal writing, video journaling, portfolio, group discussions, and online discussion. However, using photo voice as a tool for reflection to promote EFL pre-service teachers’ professional role identity in teaching practicum remains scarcely reported in the literature. To fill this gap, this study attempts to investigate how photovoice mediated self reflection could engage an EFL pre-service teacher in making a sense concerning her professional roles identity. Drawing on qualitative data gained from photovoice mediated reflection and multiple informal talks, this phenomenological case study reveals two major themes (1) teachers as manager: entertainer and (2) teacher as assessor: the development of teacher assessment identity. This study suggests that photovoice based self reflection allow a pre-service teacher to reconstruct her professional role identity without changing her perception as a teacher. By doing this, a pre-service teacher is more aware concerning her professional role identity so as to keep her professional development.